Effect of Learning Model Savi Assisted Media Kabaca (Calendar Picture Story) of Skills Reading Understanding of Stories - Lutfiana Rahmatsani (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of Learning Model SAVI aided KABACA mediaon reading comprehension skills of fourth grade students of SD Negeri Keji 2 Muntilan,Magelang Regency. This research is a type ofresearch pre-experimental (One Grouppretest posttest). The research subjects were selected by- nonprobability samplingsaturated sampling model. Samples were taken as many as 24 students. The method ofdata collection was done by using test questions in the form of giving pretest and posttestreading comprehension skills. Test the validity of the pretest and posttest questionsusing theformula, product moment while the reliability test uses the formula CronbachAlpha. The analysis prerequisite test used the normality test using theformulaKolmogorov-Smirnov. Data analysis used non-parametric statistical techniques WilcoxonSign rank test. The results of this study indicate that the calculation of the averagevalueposttest of 87 is greater than the averagevalue pretest of 57, this is evidenced by theresults of thetest analysis Wilcoxon with thevalue Asymp. Sig. (2 tailed) obtained 0.000<0.05 with a Z score of -4.297. Based on the data obtained, it is concluded that the SAVIlearning model assisted by KABACA media has a positive effect on the readingcomprehension skills of fourth grade students of SD Negeri Keji 2 Muntilan, MagelangRegency.